Postcard from Margaret Ripley to her sister, sent 19 March 1915... - whatsthatpicture from... (Wikimedia Commons, 2011)
Notice image issue de Wikimedia Commons. Titre: Postcard from Margaret Ripley to her sister, sent 19 March 1915 (6267150643). Sent by a nurse, Margaret Ripley, to her sister back in England. Here's another card addressed to Nurfield House, now identified as being on Church Lane, Kenley by EastMarple1. As far as I can tell (corrections and additions welcome) this reads: " Many thanks for letter received yesterday. Mauds parcels arrived too have just written her. Awful today windy & snow, looking forwards to coming home in 7[?] weeks & must then look out for a job. Can't say I have learnt much French awful language and everything else, food included the only decent stuff we have is English & we have to [???] that! " For more details of the story behind this album see www.flickr.com/photos/whatsthatpicture/sets/7215762769463...
Licence CC BY 2.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; église; transport